Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 4369 species occurrences available in GBIF matching the query: { "Geometry" : [ "POLYGON((58.875732 23.757695,58.886718 23.511107,58.669738 23.422928,58.400573 23.508589,58.304443 23.709924,58.631286 23.823038,58.875732 23.757695))" ] } The dataset includes 4369 records from 52 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002140-150831095807960/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences